Designing a Cross-Sector Change Management Framework for Coordinating Agile Technology Deployments (International Journal of Scientific Research in Science and Technology, 2024)
This paper addresses the critical challenge of coordinating agile technology deployments across multiple sectors by proposing an integrated change management framework. Traditional approaches often treat agile methodologies and change management separately, limiting their effectiveness in complex, cross-sector environments characterized by diverse organizational cultures, regulatory requirements, and stakeholder priorities. Through an extensive literature review, the paper identifies the limitations of existing models and highlights the need for a harmonized approach that embeds structured change processes within agile delivery cycles. The proposed framework features a modular architecture composed of strategic governance, operational coordination, and adaptive execution layers. It defines clear roles, including cross-sector change leads and sector representatives, to ensure accountability and collaboration. A cyclical process workflow integrates change enablement with iterative development, fostering continuous engagement and sustainable adoption. The framework’s flexibility and scalability make it adaptable to various project complexities and organizational contexts. This integrative approach advances both theoretical understanding and practical application, providing a pathway for improved success in cross-sector agile technology initiatives.